Determination of the relationship between ultrasonographic measurements of longissimus dorsi, backfat and body wall thickness with body weight and testicular morphometry in breeding bucks - Boey, Jin Wern (2016)
The relationship between ultrasonographic measurements of the longissimus dorsi muscle, backfat and body wall thickness with body weight and testicular morphometry was studied in 16 breeding bucks consisting of Boer as well as crossbreds for meat and dairy purposes. All animals were at least 2-years-old. Ultrasound measurements were taken for fat and muscle depths between the 12th and 13th thoracic vertebrae, 3rd and 4thlumbar vertebrae and between 12th and 13th ribs 12.7 cm distal to the dorsal vertebral processes to measure body wall thickness. Vernier caliper was used to measure testicular length (L, cm), width (W, cm) and height (H, cm). Scrotal circumference was measured with a flexible plastic tape. The firmness of the testicles was determined by palpation. Image J (version 1.49) was used to accurately measure the ultrasound images. Testicular volume was calculated using the formula: Volume= 0.5233 x L x W x H while the daily sperm output (109/day), DSO = (0.024 x testicular volume) – 1.26; in which the total testicular volume represents the sum of the right and left testicular volume. Pearson’s correlation (SPSS 23) showed that the fat depth of left thoracic area was correlated with the right testicular volume (0.497, P = 0.05). Meanwhile, the fat depth at the right thoracic area was correlated with the right testicular length (P = 0.031). Overall, bodyweight, muscle and fat depths do not have a correlation with testicular morphometry. Therefore, these measurements can only be used to evaluate carcass traits and not fertility. Additionally, body weight was correlated with thoracic circumference (0.824, P < 0.05) as well as left (0.722, P = 0.02) and right (0.543, P = 0.03) longissimus dorsi muscle depth at the area between the 12th and 13th thoracic vertebrae.